Pentingnya Materi Cuaca dan Musim dalam Meningkatkan Kepedulian Siswa terhadap Lingkungan - Agresia Desti; Firana Fiwa; Siti Aisyah; Afriza Media; Ari Suriani (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Weather and seasons play an important role in elementary school learning to increase students' awareness and concern for the environment from an early age. Students are taught to understand the relationship between weather phenomena and seasonal changes and how both affect the environment. The purpose of this article is to explain why the topic of weather and seasons is important for elementary school education, examine the learning approaches that can be used, and show how this learning can encourage students to care about the environment. It is hoped that this article will help PGSD students as prospective educators in creating learning that is not only cognitive but also affective and psychomotor. This is based on the theory of contextual learning and character education.